Atomistic Simulations on Metal Rod Penetrating Thin Target at Nanoscale Caused by High-Speed Collision - Yong-Chao Wu (MDPI AG, 2021)
The penetration process has attracted increasing attention due to its engineering and scientific value. In this work, we investigate the deformation and damage mechanism about the nanoscale penetration of single-crystal aluminum nanorod with atomistic simulations, where distinct draw ratio (<semantics>∅</semantics>) and different incident velocities (up) are considered. The micro deformation processes of no penetration state (within 2 km/s) and complete penetration (above 3 km/s) are both revealed. The high-speed bullet can cause high pressure and temperature at the impacted region, promoting the localized plastic deformation and even solid-liquid phase transformation. It is found that the normalized velocity of nanorod reduces approximately exponentially during penetration (up < 3 km/s), but its residual velocity linearly increased with initial incident velocity. Moreover, the impact crater is also calculated and the corresponding radius is manifested in the linear increase trend with up while inversely proportional to the <semantics>∅</semantics>. Interestingly, the uniform fragmentation is observed instead of the intact spallation, attributed to the relatively thin thickness of the target. It is additionally demonstrated that the number of fragments increases with increasing up and its size distribution shows power law damping nearly. Our findings are expected to provide the atomic insight into the micro penetration phenomena and be helpful to further understand hypervelocity impact related domains.